TRANSFORMASI EKONOMI WILAYAH PERBATASAN INDONESIA MELALUI PENGUATAN INFRASTRUKTUR, KOLABORASI LINTAS NEGARA, DAN PEMBERDAYAAN MASYARAKAT LOKAL - Melyana R Pugu (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2026)
This study examines the economic transformation of Indonesia’s border regions through infrastructure strengthening, cross-border collaboration, and local community empowerment. Border regions are no longer viewed merely as peripheral areas or territorial boundaries, but as strategic spaces with the potential to become new centers of regional economic growth. However, many Indonesian border areas still face structural challenges, including limited infrastructure, weak local economic capacity, dependence on neighboring countries, inadequate cross-border governance, and restricted access to markets, capital, technology, and information. This study employs a library research method with a descriptive, qualitative approach, reviewing relevant scholarly articles, government reports, policy documents, and recent literature on border development, regional economies, infrastructure, cross-border cooperation, and community empowerment. The findings indicate that infrastructure development plays a fundamental role in improving connectivity, reducing regional isolation, lowering logistics costs, and expanding access to public services and economic opportunities. Cross-border collaboration contributes to strengthening legal trade, regional mobility, tourism, investment, and people-to-people relations. Meanwhile, local community empowerment is essential to ensure that border communities become active economic actors rather than passive beneficiaries of development. The study concludes that the economic transformation of Indonesia’s border regions requires an integrative development model that simultaneously connects infrastructure, cross-border cooperation, and local empowerment. Such a model is expected to promote inclusive, collaborative, and sustainable border development while strengthening national sovereignty, local welfare, and regional competitiveness.